Non-Convex Split Feasibility Problems: Models, Algorithms and Theory - Gibali, Aviv; Sabach, Shoham; Voldman, Sergey (Open Journal of Mathematical Optimization)
In this paper, we propose a catalog of iterative methods for solving the Split Feasibility Problem in the non-convex setting. We study four different optimization formulations of the problem, where each model has advantages in different settings of the problem. For each model, we study relevant iterative algorithms, some of which are well-known in this area and some are new. All the studied methods, including the well-known CQ Algorithm, are proven to have global convergence guarantees in the non-convex setting under mild conditions on the problem’s data.